Collagen-based wound dressings for the treatment of diabetes-related foot ulcers: a systematic review - Holmes C (Dove Medical Press, 2013)
Crystal Holmes,1 James S Wrobel,1 Mark P MacEachern,2 Blaise R Boles31Department of Internal Medicine, University of Michigan Medical School, 2A Alfred Taubman Health Sciences Library, University of Michigan, 3Department of Molecular, Cellular, and Developmental Biology, University of Michigan, Ann Arbor, MI, USABackground: Diabetic foot ulcers are a major source of morbidity, limb loss, and mortality. A prolonged inflammatory response, extracellular matrix degradation irregularities, and increased bacteria presence have all been hypothesized as major contributing factors in the delayed healing of diabetic wounds. Collagen components such as fibroblast and keratinocytes are fundamental to the process of wound healing and skin formation. Wound dressings that contain collagen products create a biological scaffold matrix that supports the regulation of extracellular components and promotes wound healing.Methods: A systematic review of studies reporting collagen wound dressings used in the treatment of Diabetic foot ulcers was conducted. Comprehensive searches were run in Ovid MEDLINE, PubMed, EMBASE, and ISI Web of Science to capture citations pertaining to the use of collagen wound dressings in the treatment of diabetic foot ulcers. The searches were limited to human studies reported in English.Results: Using our search strategy, 26 papers were discussed, and included 13 randomized designs, twelve prospective cohorts, and one retrospective cohort, representing 2386 patients with diabetic foot ulcers. Our design was not a formal meta-analysis. In those studies where complete epithelialization, 58% of collagen-treated wounds completely healed (weighted mean 67%). Only 23% of studies reported control group healing with 29% healing (weighted mean 11%) described for controls.Conclusion: Collagen- based wound dressings can be an effective tool in the healing of diabetic foot wounds. The current studies show an overall increase in healing rates despite limitations in study designs. This study suggests that future works focus on biofilms and extracellular regulation, and include high risk patients.Keywords: bio films, matrix, wound healing, scaffold, dressings